Novel diversity within marine Mamiellophyceae (Chlorophyta) unveiled by metabarcoding - Margot Tragin (Nature Portfolio, 2019)
Abstract Mamiellophyceae (unicellular green algae) are a key phytoplankton group in coastal waters. Although extensively studied over the last 20 years, the overall oceanic distribution of the major species/clades is still poorly known. To address this problem, we analyzed the 2014 Ocean Sampling Day (OSD) metabarcoding dataset providing sequences from the V4 hypervariable region of the 18S rRNA gene for 157 samples collected at 143 mostly coastal stations. Mamiellophyceae were found at nearly all OSD stations and represented 55% of the green microalgae (Chlorophyta) reads. We performed phylogenetic analyses of unique OSD metabarcodes (amplicon single variants, ASVs) and GenBank reference sequences from cultures and from the environment, focusing on the four most represented genera: Ostreococcus (45% of the Mamiellophyceae reads), Micromonas (34%), Bathycoccus (10%) and Mantoniella (8.7%). These analyses uncovered novel diversity within each genus except Bathycoccus. In Ostreococcus, a new clade (E) was the second most represented clade after Ostreococcus “lucimarinus”. Micromonas could be separated into nine clades, exceeding the six species and candidate species already described. Finally, we found two new environmental clades within Mantoniella. Each Mamiellophyceae clade had a specific distribution in the OSD dataset suggesting that they are adapted to different ecological niches.